Vehicle power supply management strategies - A. V. Puzakov (Вестник СибАДИ, 2023)
Introduction. To optimize the performance of the vehicle electrical system, it is necessary to improve the control principles and strategies. The control principles may be based on voltage constancy, ensuring battery charge, reducing fuel consumption, etc.Materials and methods. A distinctive feature of the first level control strategy is the absence of additional sensors in the power supply system. Their occurence led to the emergence of the second level control strategy aimed at ensuring the starter battery charge, which is achieved by organizing the interaction between the electronic engine control unit and the generator. In the control strategy of the third level the first place is given to the reduction of the vehicle fuel consumption. The target functions of the listed control strategies are considered.Results. The fourth level management strategy, the purpose of which is to reduce the costs of power supply system operation at all stages of the life cycle, is proposed. The structure of power supply system operation costs is considered, which includes the costs of fuel overconsumption caused by malfunctions in the operation of units, as well as the costs of maintenance, diagnostics, repair (replacement) and utilization.Discussion and conclusions. Practical application of the proposed strategy will make it possible to take into account all types of costs and minimize the cost of operating the power supply system for both vehicles with internal combustion engines and hybrid and electric vehicles, in which electricity is even more important.